Hydrological drought index based on reservoir capacity – Case study of Batujai dam in Lombok Island, West Nusa Tenggara, Indonesia - Yasa I Wayan (Journal of Water and Land Development, 2018)
Hydrological drought index analysis has been widely developed and applied for the development of water resources. The island of Lombok, which is largely a dry land, requires a significant hydrological drought index to be sourced from measurable data analysis. This research focused aims to obtain hydrological drought index in Lombok Island using the capacity change of reservoir. The analysis includes reservoir data especially in the event of El-Nino. The main parameters analysed in this work are data homogeneity, decrease line of reservoir volume, increase in the line of reservoir volume, reservoir volume deficit, and hydrological drought index (RDI). The basic equation uses the water balance in the reservoir, which is the inflow–outflow and change of reservoir. The results of the analysis show that in the event of El-Nino, the drought hydrological index indicates different levels depending upon the water level of the reservoir. The criteria for the drought level are as follows: weak RDI = from −0.46 to −0.01 at an reservoir elevation of 90.88 to 92.33 m a.s.l, moderate RDI: from −0.59 to −0.46 at water level of reservoir from 90.27 to 90.88 m a.s.l, sever RDI: from −0.80 to −0.59 at water level of reservoir from 88.83 to 90.27 m a.s.l. and very severe RDI: from −0.89 to −0.80 at water level of water reservoir 87.78–88.83 m a.s.l. The duration of drought was 9 months, i.e., from February to November.